Alkyl detection facilitated by a DNA conjugate with an α-hemolysin nanopore. Issue 1 (21st December 2015) - Hu, Zheng-Li; Cao, Chan; Wang, Hui-Feng; Yan, Bing-Yong
Abstract : A novel α-hemolysin nanopore (α-HL) based strategy for the detection of an alkyl linker at the single-molecule level. Abstract : Herein an α-hemolysin nanopore was utilized to detect a DNA conjugate, where a propyl linker was attached to the 20-mer oligonucleotides at each end of an individual strand. The studies showed the alkyl linker produced a clear current change when translocating through the protein pore, which could be used to sense and identify small organic molecule at the single-molecule level.